Sistem Pendukung Keputusan Pemilihan Karyawan Tetap pada Trinity Teknologi Nusantara Dengan Metode Moora - Amri Juanda; Fricles A Sianturi (Jurnal Ilmu Komputer dan Sistem Informasi (JIKOMSI), 2020)
PT. Trinity Teknologi Nusantara is a company engaged in internet services, covering the areas of Medan, Deli Serdang, Simalungun, Binjai and its surroundings. The reality in the field is that the office is not ready to choose permanent employees. Manual administrative problems resulted in less efficiency in assigning permanent employees at PT. Trinity Teknologi Nusantara. Therefore, the authors took the initiative to create a system that can assist the office in making a decision to determine permanent employees, so that it can be more efficient in its implementation. The comparison of the Moora method with other methods found in the Decision Support System is that the MOORA method is very simple, stable, and strong, even this method does not require an expert in mathematics to use it and requires simple mathematical calculations. Besides that, the Moora method also has more accurate and targeted results in helping decision making. When compared to other methods, the MOORA method is even simpler and easier to implement